See also murder : a Marjorie Trumaine mystery - Sweazy, Larry D. (Seventh Street Books, an imprint of Prometheus Books, 2015)
"In 1964, a grisly murder is committed in the small town of Dickinson, North Dakota. Erik and Lida Knudsen are found murdered in their bed, their throats slit. Sheriff Hilo Jenkins is called to the scene and discovers a strange copper amulet clasped in Erik's hand. Knowing that his friend Marjorie Trumaine is a skilled researcher and professional indexer, Jenkins asks for her help in investigating the possible meaning of the amulet with its unusual markings. As she gets closer to the truth, Marjorie feels increasingly threatened, knowing the killer will stop at nothing to cover his tracks"--